The Power of Online Proton Transfer Reaction - Mass Spectrometry (PTR-MS) Measurement of Odorous Emissions from a Pig House - K. Van Huffel; M. Hansen; A. Feilberg; D. Liu; H. Van Langenhove (Chemical Engineering Transactions, 2014)
Online monitoring of odorous compounds in the ventilation air was applied in an experimental pig house in Denmark. The measurements were executed by proton-transfer-reaction – mass spectrometry (PTR-MS) while grab samples are used to confirm the identity of the compounds. Sorbent tubes samples were analysed by gas chromatography – mass spectrometry analysis (GC-MS) and Tedlar bags samples by gas chromatography – sulfur chemiluminescence detector (GC-SCD). For three target odorants, dimethyl sulfide, propanoic acid and p-cresol, the reproducibility after averaging over 1 hour was in the same order of magnitude for both grab and continuous sampling (